Determinants of symptom interval in childhood cancer. Issue 6 (June 1993) - Saha, V; Love, S; Eden, T; Micallef-Eynaud, P; MacKinlay, G
Abstract : The duration of symptoms before diagnosis (lag time) was defined for 184 of 236 children diagnosed as having a malignancy at the Royal Hospital for Sick Children, Edinburgh for the time period January 1982 until December 1990. The natural logarithm of the lag time was correlated with age, gender, diagnostic group, white cell count in acute leukaemia, clinical stage of disease in solid tumours, and event free survival. Age was significantly associated with lag time, older children presenting later. In the diagnostic groups, mean lag time ranged from 2.8 weeks in nephroblastoma to 13.3 weeks for brain tumours. Diagnostic group was predictive for lag time after adjustment for age, with for example, a significantly longer lag time for those with brain tumours. However lag time was not predictive of event free survival and it is likely that lag time has other major determinants. When compared with previous studies, there also appears to be a regional variation in lag time for diagnostic groups. It seems likely that this is a reflection of geographical difference in the structure of health systems and is therefore yet another important determinant.